Imidazobenzoxazin‐5‐ones as thermal latent curing agents for thermosetting epoxy resins. Issue 21 (6th August 2016) - Kudo, Kenji; Furutani, Masahiro; Arimitsu, Koji
Abstract : A novel thermal latent curing agent with good compatibility towards epoxy resins was developed. It was found that this latent curing agent is converted to the corresponding imidazole via a ring‐opening reaction. Epoxy resin compositions consisting of the latent curing agent have superior curability at 150 °C and a long shelf life at room temperature.